Formulation and characterization of chewable tablets of paracetamol and metoclopramide hydrochloride - Kumar, D; Goswami, D S; Tomar, P; Kaur, S (Journal of Applied Pharmaceutical Research, 2014)
The present study was aimed to formulate and characterized chewable tablets of Paracetamol and Metoclopramide hydrochloride. Paracetamol and Metoclopramide hydrochloride is an oral fixed dose combination for the preparation of chewable tablets used to treat the symptoms of migraine as it comply with physicochemical properties require to improve the effectiveness of therapeutic agent, better bioavailability, improved patient acceptance (especially pediatrics) through pleasant taste, patient convenience; need no water for swallowing, fasten the absorption of drug and for rapid onset of action. The investigation was carried out to study the effect of different proportion of Avicel 101, Avicel 102 and moringa gum, which are superdisintegrating agents. The chewable tablets of Paracetamol and Metoclopramide hydrochloride were prepared by wet granulation method. Several physicochemical parameters like thickness, diameter, hardness, %weight variation, %loss in weight, drug content, disintegration time, in vitro dissolution studies, kinetics of drug release and stability studies for all the formulations were studied and were found within the acceptance limits. Formulation F7 (containing moringa gum 1%) showed the best cumulative drug release and disintegration time of 56 secs.